Determinants of Risk Factors for Placenta Previa at Government General Hospital Dr. M. Djamil Padang, 2020-2022 - Zulfa Safitri; Fitrayeni; Abdiana (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2026)
Placenta previa is a placenta that partially or completely covers the ostium uteri internum. Placenta previa accounts for 25% of antepartum hemorrhage. Risk factors associated with placenta previa are age, parity, interpregnancy interval, history of cesarean section, history of curettage, and history of placenta previa. The purpose of this research was to determine the risk factors associated with the incidence of placenta previa at Government General Hospital Dr. M Djamil Padang. The type of this research was quantitative with case control design. The sample was divided into two groups, the case (placenta previa) and the control (without placenta previa). The sample size was calculated using the unpaired categorical variable formula and obtained 160 samples with a ratio of cases:controls (1:1). The sampling technique used was simple random sampling. Data were obtained from the patient’s medical records. Univariate and bivariate data was analyzed with Chi-square test (p≤0,05). The results of this research showed that there was an association between maternal age (p=0,000, OR=3,621, 95% confidence interval, 1,828-7,175), parity (p=0,000, OR=3,646, 95% confidence interval, 1,898-7,001), interpregnancy interval (p=0,005, OR=3,370, 95% confidence interval, 1,498-7,585), history of cesarean section (p=0,000, OR=14,636, 95% confidence interval, 6,603-32,434), history of curettage (p=0,014, OR=3,203, 95% confidence interval, 1,323-7,755), and history of placenta previa (p=0,012, OR=11,286, 95% confidence interval, 1,409-90,395) with the incidence of placenta previa. Risk factors such as age, parity, interpregnancy interval, history of cesarean section, history of curettage, and history of placenta previa have a significant association with the incidence of placenta previa. Healthcare providers are expected to provide education on the importance of recognizing and avoiding risk factors associated with placenta previa.